Cell line modeling to study biomarker panel in prostate cancer. Issue 3 (2nd November 2015) - NickKholgh, Bita; Fang, Xiaolan; Winters, Shira M.; Raina, Anvi; Pandya, Komal S.; Gyabaah, Kenneth; Fino, Nora; Balaji, K.C.
Abstract : Background: African–American men with prostate cancer (PCa) present with higher‐grade and ‐stage tumors compared to Caucasians. While the disparity may result from multiple factors, a biological basis is often strongly suspected. Currently, few well‐characterized experimental model systems are available to study the biological basis of racial disparity in PCa. We report a validated in vitro cell line model system that could be used for the purpose. Methods: We assembled a PCa cell line model that included currently available African–American PCa cell lines and LNCaP (androgen‐dependent) and C4‐2 (castration‐resistant) Caucasian PCa cells. The utility of the cell lines in studying the biological basis of variance in a malignant phenotype was explored using a multiplex biomarker panel consisting of proteins that have been proven to play a role in the progression of PCa. The panel expression was evaluated by Western blot and RT‐PCR in cell lines and validated in human PCa tissues by RT‐PCR. As proof‐of‐principle to demonstrate the utility of our model in functional studies, we performed MTS viability assays and molecular studies. Results: The dysregulation of the multiplex biomarker panel in primary African–American cell line (E006AA) was similar to metastatic Caucasian cell lines, which would suggest that the cell line model could be used to study an inherent aggressive phenotype in African–American men with PCa. We had previously demonstrated that Protein kinase D1 (PKD1) is a novel kinase that is down regulated in advanced prostate cancer. We established the functional relevance by over expressing PKD1, which resulted in decreased proliferation and epithelial mesenchymal transition (EMT) in PCa cells. Moreover, we established the feasibility of studying the expression of the multiplex biomarker panel in archived human PCa tissue from African–Americans and Caucasians as a prelude to future translational studies. Conclusion: We have characterized a novel in vitro cell line model that could be used to study the biological basis of disparity in PCa between African–Americans and Caucasians. Prostate 76:245–258, 2016 . © 2015 Wiley Periodicals, Inc.